Purification technology design, biochemical and immunological characteristics of the recombinant chimeric antigen for evaluation of T cell immunity against coronavirus infection - V. V. Kopat; A. A. Riabchenkova; E. L. Chirak; E. R. Chirak; A. I. Saenko; I. V. Kudryavtsev; A. S. Trulioff; T. V. Savin; E. V. Zueva; A. S. Simbirtsev; A. A. Totolyan; I. V. Dukhovlinov (Медицинская иммунология, 2024)
Diagnosis of specific T cell immunity to the antigenic determinants of SARS-CoV-2 in patients seems to be an increasingly important task due to accumulation of data about the role of T cell immune response in course of coronavirus infection and clearance of SARS-CoV-2 in case of secondary infection. Previously, we designed the recombinant CorD_PS antigen for evaluation of T cell antiviral immunity, containing conservative and immunogenic sequences of structural proteins of the SARS-CoV-2 coronavirus. E. coli CorD_PS producing strain with stable expression of the recombinant CorD_PS antigen was obtained. Aim of the present work is to design a laboratory technology for the production of recombinant antigen CorD_PS, to control the quality of the obtained chimeric protein and to study its immunological activity. Development of the cultivation conditions for E. coli CorD_PS cells was carried out in conical flasks in LB-M_Km medium at 37 °C, then scaled in a fermenter with a volume of 30 liters. Expression was induced by the addition of IPTG. Expression was controlled in culture lysates in 12% SDS-PAGE. The resulting biomass was lysed using an ultrasonic disintegrator with followed by centrifugation. The compositions of lysing and solubilizing buffers were selected, as well as conditions for refolding of the recombinant protein. Cation exchange (SP-sepharose), hydrophobic (Butylsepharose) and exclusive (Sephacryl S-200 HR) chromatography were used sequentially to purify the dissolved protein. Protein impurities in the preparation were determined by reverse-phase HPLC and electrophoresis in 12% SDS-PAGE, residual lipopolysaccharides were determined using a gel-thrombin variant of the LAL test, residual proteins of the producer strain were determined by enzyme immunoassay, residual DNA of the producer strain was determined by binding with PicoGreen dye. Specificity was controlled by indirect enzyme immunoassay. The evaluation of cytokine production by CD4+T lymphocytes in response to their stimulation by recombinant antigen ex vivo was performed on a flow cytofluorimeter. The biomass yield during cultivation of E. coli CorD_PS in a 30L fermenter was up to 20 g/L for 4 hours of 0.1 mM IPTG induction. Sequential washing of inclusion bodies from bacterial cellular components and their subsequent solubilization in a buffer containing 8 M urea allowed to obtain a solution of denatured antigen with a concentration of 10 mg/mL. The efficiency of refolding by dilution was 75%. After three stages of chromatographic purification, protein samples with a concentration of 1.2-1.4 mg/mL, HPLC purity of 98.43%, corresponding to key quality parameters according to the OFS.1.7.1.0007.15, were obtained. The recombinant antigen showed specific binding to a sample of the First WHO International Standard and sample Company Reference Standard No. 3 of anti- SARS-CoV-2 human immunoglobulins in a specified concentration range. CD4+T lymphocytes effectively responded to recombinant antigen treatment by increasing IFNγ production. The optimal concentration of recombinant coronavirus antigen was 5 μg/mL. The developed technological process makes it possible to obtain 5-7 grams of coronavirus recombinant CorD_PS antigen in one cultivation cycle in 30 liters of fermentation medium with key quality parameters according to the OFS.1.7.1.0007.15. As a result of specific immunological activity studies of the recombinant coronavirus antigen CorD_PS, the concept of its possible use as a diagnostic tool for determining the formation of a T cell immune response was confirmed.